2018
DOI: 10.1016/j.schres.2017.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood ethnic density and psychosis — Is there a difference according to generation?

Abstract: BackgroundFor different migrant groups living in an area with few people from the same ethnic background is associated with increased psychosis incidence (the ethnic density effect). We set out to answer the question: are there generational differences in this effect?MethodsAnalysis of a population based cohort (2.2 million) comprising all those born 1st January 1965, or later, living in Denmark on their 15th birthday. This included 90,476 migrants from Africa, Europe (excluding Scandinavia) and the Middle Eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 31 publications
(51 reference statements)
4
59
0
Order By: Relevance
“…Despite the increase in the white non-British population in the UK, particularly since the expansion of the European Union in 2004 and ease of migration from Eastern Europe, we found weak evidence of increased risk of psychosis between the white non-British and white British ethnic groups. Our findings in this group are in keeping with two recent studies (Kirkbride et al, 2017;Schofield et al, 2017), which both found that non-British white ethnic groups in the UK and migrants from elsewhere in Europe to Denmark were not at increased risk of psychosis. This may also be because the white non-British patients may experience a less stressful acculturation process and lower perceived discrimination (Schofield et al, 2017) within Europe.…”
Section: Psychological Medicinesupporting
confidence: 92%
“…Despite the increase in the white non-British population in the UK, particularly since the expansion of the European Union in 2004 and ease of migration from Eastern Europe, we found weak evidence of increased risk of psychosis between the white non-British and white British ethnic groups. Our findings in this group are in keeping with two recent studies (Kirkbride et al, 2017;Schofield et al, 2017), which both found that non-British white ethnic groups in the UK and migrants from elsewhere in Europe to Denmark were not at increased risk of psychosis. This may also be because the white non-British patients may experience a less stressful acculturation process and lower perceived discrimination (Schofield et al, 2017) within Europe.…”
Section: Psychological Medicinesupporting
confidence: 92%
“…Fourteen studies were conducted (45%) in the UK 9,11,[25][26][27][28][29][30][31][32][33][34][35][36] , eight (26%) in the Netherlands [37][38][39][40][41][42][43][44] , and four (13%) in Sweden [45][46][47][48] . Of the remaining five (16%), two were conducted in Denmark 49,50 , and one of each in the USA 51 , Canada 52 , and Australia 53 .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The majority were retrospective epidemiological studies (n=26, 84%) 9,11,[25][26][27][28][29][30][31][32][33][34][35][36][39][40][41][42][45][46][47][48][49][50]52,53 . Of these, most were cross-sectional and six (four datasets) used longitudinal methods 32,[46][47][48][49][50] . All of these studies were conducted in a neighbourhood context with the exception of one which considered a school setting 46 .…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations